ESTRUS INDUCTION, FOLLICULAR DYNAMICS AND FERTILITY RESPONSE TO MID-CYCLE PGF2a, CIDRAND OVSYNCH PROTOCOLS IN SUBFERTILE GIRAND CROSSBRED COWS - HADIYA, K K; DHAMI, A J; NAKRANI, B B; LUNAGARIYA, P M (The Indian Journal of Animal Reproduction, 2023)
This study was carried out on 36 infertile (subestrus and repeat breeders) Girand HF x K crossbred cattleof University farm using three estrus synchronization protocols, viz., Mid-cycle PGF2n, Ovsynch and CIDR,to evaluate estrus response and conception rates clinically and through transrectal ultrasound scanning, andthe findings were compared with those of 24 untreated cyclic cows. Six subestrus/repeat breeding cows eachof Gir & crossbreds (6x2 = 12) having mid cycle mature CL were treated with single i/m injection of 500 ±gcloprostenol, and fix timed Al (FTAI) was performed at 72 and 96 hrs post-treatment. Similarly, six infertilecyclic Girand crossbred cows each (6x2 =12) were treated with standard CIDR protocol and equal numbers(6x2 =12) with Ovsynch protocol using FTAI on day 9 and 10. Ovarian and uterine changes were monitoredusing transrectal ultrasound scanning (USG) on alternate days till induced estrus/FTAI, and then at weeklyinterval till day 42 post-Al. Estrus induction response was 100 % with all three synchronization protocolsas seen clinically and through USG. The conception rates of 12 subfertile cows, each subjected to CIDR,Ovsynch and Mid-cycle PGF2u treatment protocols were 41.66, 41.66 and 33.33 %, respectively, at Inducedestrus. The corresponding conception rates at second cycle post-treatment were 28.57, 42.85 and 25.00 %;and at third cycle 40.00, 50.00 and 33.33 %, with the overall conception rates of 3 cycles as 75.00, 83.33 and66.66 %. In untreated cyclic control cows, the conception rates at first, second and third service and overall of3 services were 20.83, 21.05, 26.66 and 54.16 %, respectively. The mean CL size on the day of mid-cycle PGinjection was largest (14.0200.46 mm) and that of follicle smallest (4.2200.42 mm), which changed drastically(P
Keywords: Cows; Estrus induction; Fertility; Follicular dynamics; Ovsynch; CIDR; Mid-cycle PG protocol